2011
DOI: 10.1371/journal.pone.0022749
|View full text |Cite
|
Sign up to set email alerts
|

Investing in Threatened Species Conservation: Does Corruption Outweigh Purchasing Power?

Abstract: In many sectors, freedom in capital flow has allowed optimization of investment returns through choosing sites that provide the best value for money. These returns, however, can be compromised in countries where corruption is prevalent. We assessed where the best value for money might be obtained for investment in threatened species that occur at a single site, when taking into account corruption. We found that the influence of corruption on potential investment decisions was outweighed by the likely value for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In the statistical analyses, management budgets are US$ per km 2 per year while controlling for purchasing power and likely losses to corruption (Garnett et al . ). Budgets could not be partitioned according to anti‐poaching, outreach, fence repairs, road maintenance, etc.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the statistical analyses, management budgets are US$ per km 2 per year while controlling for purchasing power and likely losses to corruption (Garnett et al . ). Budgets could not be partitioned according to anti‐poaching, outreach, fence repairs, road maintenance, etc.…”
Section: Methodsmentioning
confidence: 97%
“…), declining purchasing power of external funds (Garnett et al . ) or worsening corruption (Garnett et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, others have found that areas with the highest performance certainty (with a high likelihood that investments would lead to effective conservation accounting for governance aspects) were prioritized over areas with higher biodiversity values or higher threats . In any case, all these prioritization studies appear to conclude that global conservation should invest in nations with a high quality of governance . However, should only sites with a high quality of governance be allocated funding, or could conservationists aim for effective outcomes by the alternative strategy of setting policy conditions for their funding?…”
Section: Prioritizing Actionmentioning
confidence: 99%
“…17,73 In any case, all these prioritization studies appear to conclude that global conservation should invest in nations with a high quality of governance. 16,[73][74][75] However, should only sites with a high quality of governance be allocated funding, or could conservationists aim for effective outcomes by the alternative strategy of setting policy conditions for their funding? This debate between selectivity and conditionality, although common and heated in other fields (Box 2), has remained largely ignored in conservation.…”
Section: Prioritizing Actionmentioning
confidence: 99%
“…The relationship between political factors and biodiversity conservation has been discussed (Laurance, 2004;Ferraro, 2005;Katzner, 2005; and evaluated empirically (Smith et al, 2003;Barrett et al, 2006;Agnew et al, 2009;Burn et al, 2011). Indicators of governance and political willingness to act have been incorporated in conservation planning as (1) the probability of success in conservation investment (McBride et al, 2007;Wilson et al, 2011), (2) as a cost (bad governance) or opportunity (good governance) in choice of priority sites (O'Connor et al, 2003;Eklund et al, 2011) and (3) as a factor that reduce the total budget invested in conservation (Garnett et al, 2011). Political governance has been debated in a global context, given the necessity of good translation of investment into conservation actions (Eklund et al, 2011), although this possibility has not been explored yet at scales below the national level.…”
Section: Introductionmentioning
confidence: 99%